An energy-efficient threshold voltage extractor with the burst-mode operation and extended long-term variations using FVF. (October 2020) - Kariman, A.R.; Ghaznavi-Ghoushchi, M.B.; Shamshiri, A.R.
Abstract: There are various circuits for extracting threshold voltage ( V t h ) of CMOS transistors. In this work, we have introduced an energy-efficient threshold voltage extractor with high precision and extended long-term variations. Considering fabrication prohibits, a switched capacitor (SC) has been used instead of a high resistive poly resistor. In order to reduce the power consumption of the V t h extractor, the circuit operates in the burst-mode (energy-efficient). Also, to reduce the glitches in the structure of the SC, a 3rd-order low-pass filter and a replica branch are used. Furthermore, the flipped voltage follower (FVF) structure extends threshold voltage variations over time to measure V t h aging via reasonable resolution data converters. The circuit has been evaluated using 65 n m standard CMOS model. The range of V th variations over 180 months is between 239.4 m V and 278.9 m V, which is equivalent to a 16.5% change. The power consumption of the entire circuit is less than 11 n W . This circuit is a good candidate to function as a benchmark for the efficiency of high-reliability circuits and aging sensors.